Determinantes do cr??dito banc??rio e os impactos do risco de cr??dito sobre a economia brasileira - Almeida, Fernanda Dantas (2016)
Banking credit plays a key role for the economic development and, therefore, it is important to understand its dynamics and its actuation for the transmission of the monetary policy. Thus, this thesis consists of two studies that aim to understand the micro and macroeconomic behavior of bank credit, investigating the main determinants of bank credit as well as the interaction of the banking sector with other sectors of the economy. The microeconomic analysis aims to identify the major determinants of banking credit in the Brazilian economy, considering the influence of specific characteristics of the financial institutions and monetary policy in the period 2001 to 2012. This paper contributes with the literature by showing that there was no relevant impact from the macroeconomic environment on the credit supply in the analyzed period. The government has adopted a countercyclical credit policy mismatched from prevailing macroeconomic conditions. In turn, the macroeconomic analysis investigates the effects of credit risk for the financial intermediation and how this risk is transmitted to other agents in the economy. The DSGE model with financial frictions of Gertler and Karadi (2011) was modified to incorporate the risk of default given by the probability of non-payment of loans granted by the bank. This study contributes to the literature by deriving the probability of default of firms endogenously in the model, unlike most of the studies that assume it as exogenous. Moreover, as the model assumes two different interest rates for the two kinds of borrowers ("good" and "bad" payers), it allows the analysis of the impacts of the borrowers??? quality on the overall interest rate on loans. As a result, we identified a countercyclical default rate, which compensates the bank for the lost with ???bad??? payers.